HUC-MSCs combined with platelet lysate treat diabetic chronic cutaneous ulcers in Bama miniature pig - Yunyi Gao; Lihong Chen; Yan Li; Shiyi Sun; XingWu Ran (Regenerative Therapy)
Human umbilical cord mesenchymal stem cells (HUC-MSCs) and platelet lysate (PL) shows potential of wound healing. However, MSCs in combination with PL for wound healing is still lacking. In this study, we presented high glucose cultured wound related cells to mimic diabetic chronic ulcers (DCU) cells, wound healing indicators and the TGFβ/Smad signaling pathway were detected by PL cultured HUC-MSC supernatant (MSC-Sp) in vitro. In vivo study, diabetes was induced in pigs feeding a high-energy diet and multiple injections of streptozotocin (125 mg/kg). Chronic wounds were created on both sides of the backs of seven pigs by surgical creation and foreign body compression for eight weeks before treatment. The wounds were treated with saline control (N = 11), PL (N = 11), HUC- MSCs (N = 18, 6 × 106/mL/cm2), and PL + HUC-MSCs (N = 18, 6 × 106/mL/cm2) respectively. Tissue samples were collected to observe new collagen, neovascularization, wound healing factors, and the TGFβ/Smad signaling pathway. The resulting PL-cultured MSC-Sp promoted the proliferation of keratinocytes, fibroblasts, and vascular endothelial cells and inhibited the TGFβ1/TGFβ3 ratio, upregulated VEGF-α and PDGF-BB production by keratinocytes and fibroblasts, and downregulated the expression of CD86, IL-6, and TNF-α in RAW264.7 cells. PL + HUC-MSCs had the best wound healing rate in vivo, and promoted collagen formation, neovascularization, and inflammation, regulated the balance between IL-6/TGFβ1 and IL-6/Arg-1 and upregulated the expression of VEGF-α and TGFβ1. In summary, PL + HUC-MSCs had a better wound healing effect than HUC-MSCs or PL treatment alone by regulating the IL-6/Arg-1 and IL-6/TGFβ1 balance and upregulating TGFβ1, VEGF-α, Col1, and α-SMA.